2006
DOI: 10.1103/physrevstab.9.081301
|View full text |Cite
|
Sign up to set email alerts
|

Quasistatic capillary discharge plasma model

Abstract: A one-dimensional, quasistatic model of a capillary discharge plasma has been developed. Such a plasma is useful as a medium to generate plasma waves for acceleration of electrons via processes such as laser wakefield acceleration or plasma wakefield acceleration. Another important characteristic of the plasma is its intrinsic parabolic density distribution near the center of the capillary, which can channel a laser beam along the capillary. The model is intended to be a design tool to aid in the selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…6, the relation n e = Z eff n i has been considered. On the other hand, a Debye sheath arises in a plasma even when the electrons have a temperature comparable to that of the ions, since they are much lighter [20]. As already pointed out, for the plasma discharges of our interest we are going to consider the electrons and the ions at the same temperature since the thermalization through the electron-ion collisions occurs on a timescale much shorter than that of the discharge current.…”
Section: A Heat Ratementioning
confidence: 99%
See 1 more Smart Citation
“…6, the relation n e = Z eff n i has been considered. On the other hand, a Debye sheath arises in a plasma even when the electrons have a temperature comparable to that of the ions, since they are much lighter [20]. As already pointed out, for the plasma discharges of our interest we are going to consider the electrons and the ions at the same temperature since the thermalization through the electron-ion collisions occurs on a timescale much shorter than that of the discharge current.…”
Section: A Heat Ratementioning
confidence: 99%
“…The electrostatic Debye sheath is a layer in the plasma with a greater density of positive ions, and hence an overall excess of positive charge, that balances an opposite negative charge on the surface of the material with which it is in contact. The thickness of such a layer is several Debye lengths thick, depending on the electron temperature and density [20]. The Debye sheath in the case of the plasma discharge capillary is placed at the interface between the bulk plasma and the capillary internal surface.…”
Section: A Heat Ratementioning
confidence: 99%
“…At some point r = r p1 , the plasma density fell off to zero, forming the vacuum channel (see Fig.2). In all the computations, the plasma density, extrapolated to the structure axis with the parabolic relation [21], was put to be 4.41 · 10 14 cm−3, this corresponding to the plasma wave frequency of ∼ 189 GHz.…”
Section: The Statement Of the Problemmentioning
confidence: 99%
“…In this * sotnikov@kipt.kharkov.ua; Gennadiy.Sotnikov@gmail.com case, at great times of the discharge onset, the nonuniform plasma density distribution is formed with the radial dependence obtained by numerical simulation of the discharge in ref. [20], which can be described by the parabolic relation for a considerable part of the channel section [21]. The PIC simulation of the test electron bunch acceleration with the model plasma-density dependences [20,21] has shown that the capillary discharge plasma improves the focusing of accelerated bunches [22] in comparison with the case of the uniform plasma density in the section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation